Analysis Of Cost Price Calculations Production For Pricing Selling Mother Mujiatin's Marningcorn Bukit Barian Kepahiang Village - Rika Wulandari; Herlin Herlin; Abdul Rahman (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
The aim of this research is to find out how to calculate the cost of production to determine the selling price of Ibu Mujiatin's Marning Corn Business. By using the Full Costing analysis method and determining the selling price using the cost-plus pricing method. Calculations are made based on the results of interviews and documentation of sales results. From the results of the research, calculations were carried out by Mrs. Mujiatin's corn marning business. The basic price of corn production is IDR. 144,557.- per can with the selling price determined based on the market price of Rp. 150,000,- per can. So the profit obtained is IDR. 5,443.-. Based on the Full Costing method, the cost of production for Mrs. Mujiatin's Marning Corn business in 2022 is IDR. 150,933.- per can with a production level of 596 cans. By setting the selling price at 25% of the cost of production, the selling price of marning corn will be IDR. 189,000.- Pekaleng with a profit of Rp. 38,067 per can. There is a difference in the calculation of the cost of production between business owners using the full costing method, due to factory overhead costs which are not taken into account by the business owner.